Faktor Motivasi Teori Dua Faktor Herzberg dan Tahap Motivasi Guru Pendidikan Islam - Alia Yashak; Mohamad Syafiq Ya Shak; Mohd Haniff Mohd Tahir; Dianna Suzieanna Mohamad Shah; Mohd Faisal Mohamed (USIM Press, 2024)
Vol. 5 No. 2 (2020): Jurnal Sains Insani